Saccharomyces cerevisiae as a model to confirm the ability of FTIR to evaluate the presence of protein aggregates - Magalhães, Sandra (2020)
It is known that the presence of protein aggregates in biological samples is associated with natural aging processes and age-related diseases. The objective of this technical study was to evaluate the potential of Fourier Transform Infrared Spectroscopy to identify the presence of protein aggregates in Saccharomyces cerevisiae containing high levels of protein aggregates. We acquired ATR-FTIR spectra at mid-infrared range (between 4000 and 600 cm−1) and used multivariate analysis to analyze the data. Significant differences between spectra of wild type and mutant strains in the spectral range assigned to proteins were observed. In particular, an increase in β-sheet structures in mutant strains (spectral signals at 1683 and 1628 cm−1) was observed, indicating the putative presence of protein aggregates. These results prove the capacity of FTIR to evaluate changes in protein conformation, mainly protein aggregation, in a fast, simple and non-expensive way, producing insights on the possible application of this technique to the detection of protein aggregates in human biological samples.